Western esotericism in Scandinavia - Bogdan, Henrik. (Brill Esotericism Reference Library., 2016)
This is the first encyclopaedic work on Western esotericism in Scandinavia. Structured along the lines of the Dictionary of Gnosis and Western Esotericsm (2005), it contains over 80 articles written by 47 specialists. It consists of critical overviews of all the major esoteric currents in Denmark, Finland, Norway, and Sweden, ranging from Alchemy, Anthroposophy, and Astrology, to Theosophy, Traditionalism, and UFO Movements. This ground-breaking work is of relevance not only for scholars and students of Western esotericism, but for all with an interest in alternative religious traditions and Scandinavian intellectual history.